2018
DOI: 10.1063/1.5017491
|View full text |Cite
|
Sign up to set email alerts
|

Flow of quasi-two dimensional water in graphene channels

Abstract: When liquids confined in slit channels approach a monolayer, they become two-dimensional (2D) fluids. Using molecular dynamics simulations, we study the flow of quasi-2D water confined in slit channels featuring pristine graphene walls and graphene walls with hydroxyl groups. We focus on to what extent the flow of quasi-2D water can be described using classical hydrodynamics and what are the effective transport properties of the water and the channel. First, the in-plane shearing of quasi-2D water confined bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The nonconducting model surface consists of a single layer of 5600 charge-free carbon atoms on a graphene lattice, interacting with water via the Lennard-Jones potential. ,, The conductor behavior of graphene is captured by the addition of fluctuating Gaussian charges on carbon atoms as outlined in the Results and Discussion section. We mitigate finite size effects by periodically replicating the surface in the lateral ( x , y ) directions.…”
Section: Models and Methodsmentioning
confidence: 99%
“…The nonconducting model surface consists of a single layer of 5600 charge-free carbon atoms on a graphene lattice, interacting with water via the Lennard-Jones potential. ,, The conductor behavior of graphene is captured by the addition of fluctuating Gaussian charges on carbon atoms as outlined in the Results and Discussion section. We mitigate finite size effects by periodically replicating the surface in the lateral ( x , y ) directions.…”
Section: Models and Methodsmentioning
confidence: 99%
“…The effective channel height ( h eff ), which considers the atomic size of carbon atoms, is estimated by subtracting the van der Waals size of carbon atoms from the nominal channel height, h , such that h eff = h – 3.4 Å . The number of water molecules inside the channel is selected in such a manner that it reproduces an internal pressure of 1 bar , (see Section S3 in the Supporting Information). The simulations are conducted as follows: first, water molecules and carbon atoms are heated from 10 to 300 K over 50 ps.…”
Section: Computational Methodsmentioning
confidence: 99%
“…It has been recognized that for nanopores with hydrophilic surfaces, the confined fluid viscosity increases by decreasing the confinement size; however, for nanopores with hydrophobic surfaces, the viscosity decreases by reducing the pore size. Nevertheless, recently, it has also been reported that the hydrophobic carbon surface could lead to an enhanced confined viscosity. These different phenomena and results might suggest that the surface nature is not the critical factor determining the confined fluid viscosity within the nanopore, and instead, the surface-induced molecular structure and interfacial interaction will control the viscosity.…”
Section: Introductionmentioning
confidence: 99%